Biomarkers and progress of antioxidant therapy for rare mitochondrial disorders. (2nd June 2016) - Chico, Lucia; Orsucci, Daniele; Lo Gerfo, Annalisa; Marconi, Letizia; Mancuso, Michelangelo; Siciliano, Gabriele
ABSTRACT: Introduction: In mitochondrial disorders, a group of genetic diseases associated with decreased energy production and redox imbalance, the pathogenic role of oxidative stress has been pivotal in fostering antioxidant therapy in the attempt to modify the natural history of the conditions. Areas covered: This review focuses on oxidative stress biomarkers and discusses antioxidant treatment as a potential drug strategy for effective management of mitochondrial disorders. Expert opinion: New approaches and strategies will be needed to treat patients with mitochondrial disorders. Clinical variability of mitochondrial disorders, low sample size due to their rarity, lacking data on disease natural history and the high variance of the outcome measures so far used are all factors that, in addition to the complexity of the investigated pathway and the huge number of potential combinations of antioxidants, make it necessary to optimize treatment strategy, refine the target and improve the investigation tools. New molecules have recently been studied, such as Nrf2 inducers. Combinations of antioxidant substances also seem to have a rationale in this context. Promising results come from the stimulation of mitochondrial biogenesis or by-pass the genetic block of OXPHOS complexes by alternative enzymes NADH dehydrogenase/CoQ reductase and CoQ/O2 oxidase. Finally, gene therapy approaches seem to open interesting scenarios, targeted to repair the mutated gene to complement its defect. Going ahead with well-controlled clinical trials is still necessary to define the effectiveness of current potential therapies and to design future, hopefully more effective, interventions for mitochondrial disorders.